DESCRIPTION OF STUDENTS’ ACTIVITY IN MATHEMATICS LEARNING THROUGH THE IMPLEMENTATION OF APTITUDE TREATMENT INTERACTION BASED ON COGNITIVE STYLE OF GRADE IX.2 AT SMPN 26 MAKASSAR - Mike Kusumawati (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
The study aims to describe the students’ activity in Mathematics learning through the implementation of aptitude treatment interaction based on cognitive style of grade IX.2 at SMPN 26 Makassar. The study is qualitative research. The subjects of the research are 6 students consist of high ability group of field independent cognitive style, high ability group of field dependent cognitive style, medium ability group of field independent cognitive style, medium ability group of field dependent cognitive style, low ability group of field independent cognitive style and low ability group of field dependent cognitive style. The instruments of the research are: 1) students’ activity observation sheet; 2) learning result test; and 3) interview guidance. The results of the study are 1) the research subject of high ability group of field dependent cognitive style indicates the activities conducted were paying attention to the teacher’s explanation, prefer to ask the teacher, less serious in reading books because more focusing on the teacher’s explanation, working on students’ worksheet cooperatively than individually, prefer to work on evaluation exercise individually, and pleased to present/respond students’ questions well; 2) the research subject of medium ability group of field dependent cognitive style shows the activities conducted were paying attention to the teacher’s explanation seriously, asking the teacher and students, sometimes working on students’ worksheet cooperatively and individually, delighted to work on evaluation exercise individually, presenting and responding students’ questions and learning result well; 3) the research subject of low ability group of field dependent cognitive style reveals the activities conducted were paying attention to the teacher’s explanation seriously in the beginning of learning but paying less attention to the teacher in the end, asking the teacher, delighted to work on students’ worksheet cooperatively, sometimes working on evaluation exercise by relying on students’ ability, and not presenting/responding/asking other students; 4) the research subject of high ability group of field independent cognitive style shows the activities conducted were prefer more on reading books than paying attention on the teacher’s explanation, focusing more on reading books than asking/giving comments to friend/teacher, more comfortable on working on students’ worksheet individually, focusing more and pleased in working evaluation exercise individually as well as presenting and responding students’ learning result well; 5) the research subject of medium ability group of field independent cognitive style reveals the activities conducted were delighted to obtain much information such as paying attention to the teacher’s explanation and reading books, not asking and only giving response on friends, prefer to work on students’ worksheet individually, as well as presenting and responding students’ question and learning result well; and 6) the research subject of low ability group of field independent cognitive style indicates the activities conducted were paying attention to the teacher’s explanation seriously, working on students’ worksheet individually, working on evaluation exercise individually, presenting the task result but not responding to students’ questions well, and asking students’ learning result which had been presented